Nickel oxide nanoparticles grafted with Chitosan as saturable absorber for tunable passively Q-switched fiber laser in S+/S band - Ahmad, Harith; Reduan, Siti Aisyah; Yusoff, Norazriena (Elsevier, 2018)
A tunable, passively Q-switched fiber laser using nickel oxide nanoparticles grafted onto a chitosan host (NiO/Chitosan) as saturable absorber (SA) is proposed and demonstrated for operation in the S+/S band region. The generated Q-switched pulses can be tuned from 1452 nm to 1515 nm, giving a tuning range of 63 nm. The pulses have a repetition rate from 12.3 kHz to 30.8 kHz as well as minimum pulse width and maximum pulse energy of 3.5 µs and 61.0 nJ, respectively at maximum pump power of 135.8 mW. To the best of the author's knowledge, this is the first time that tunable Q-switching operation in the S+/S band region is obtained using a NiO/Chitosan based SA.